Proliferative and nonproliferative lesions of the rat and mouse mammary, Zymbal's, preputial, and clitoral glands - Rudmann, Daniel; Cardiff, Robert; Chouinard, Luc; Goodman, Dawn; Küttler, Karin; Marxfeld, Heike; Molinolo, Alfredo; Treumann, Silke; Yoshizawa, Katsuhiko (Toxicologic pathology, 2012)
The mammary gland of laboratory rodents is an important organ for the evaluation of effects of xenobiotics, especially those that perturb hormonal homeostasis or are potentially carcinogenic. Mammary gland cancer is a leading cause of human mortality and morbidity worldwide and is a subject of major research efforts utilizing rodent models. Zymbal's, preputial, and clitoral glands are standard tissues that are evaluated in animal models that enable human risk assessment of xenobiotics. A widely accepted and utilized international harmonization of nomenclature for mammary, Zymbal's, preputial, and clitoral gland lesions in laboratory animals will improve diagnostic alignment among regulatory and scientific research organizations and enrich international exchanges of information among toxicologists and pathologists.